Brief Acrimony Scale – 8 (BACS-8) for Separated Parents – Development and Validation. Issue 8 (16th November 2020) - Rahimullah, Riyad H.; Sanri, Cagla; Halford, W. Kim; Lohan, Aditi; Petch, Jemima F.
ABSTRACT: The current study aimed to develop a reliable, valid, and condensed version of the 25-item Acrimony Scale. In a sample of 451 separated parents seeking family mediation, an Exploratory Factor Analysis showed 8 items, focusing on inter-parental hostility, loading highly on a single factor. In a second sample of 447 separated parents, a Confirmatory Factor Analysis replicated the structure. The Brief Acrimony Scale-8 (BACS-8) was correlated with co-parental conflict communication, and with parental alliance. The BACS-8 has high internal consistency, a replicable factor structure, and is potentially useful for quick, routine screening of co-parenting conflict.